"A escola como sempre sonhei" - Paula Cristina dos Santos Campos (2022)
The Professional Internship is a very important stage in the life of the teacher. It represents a great form of teaching, being a stage of constant learning both personally, professionally and socially, becoming decisive for good performance during the career of the teacher. The internship represents the last stage achieved in my long academic and personal career and played a key role in consolidating all the knowledge acquired during my training and during my practice as a practicing teacher. The teacher as a committed professional interested and motivated, should, after analyzing the context, students and objectives outline the best way forward, always trying to achieve student success and always promoting their learning. As mentioned Freire (2004, p. 573) "teaching is not a linear process of knowledge transmission, it involves the learner in an active learning process". Teachers should pay attention to all important aspects in their planning, especially in the organization and management of classes. Good planning can influence not only the good course of class, but also the learning made by students. In physical education classes should take into account the level of students, their motivation, the time of real motor commitment and requires the teacher, control, management and response to the performances of students. The internship proved to be an excellent opportunity for learning, promotion and acquisition, development of professional and personal skills, proactive attitudes in identifying and solving pedagogical problems, In order to constitute the starting point for a future integration in a new teaching group of Physical Education. Throughout this report I report the various phases of my career in school, initially as a student and later as a teacher. I also report all training and positions performed professionally. Looking at all this way I realize that life is a long and admirable process and that it is really worth living.